SIGNS IN THE LYRICS OF TAFSIR MISTIK BY ABYAN ZAKI: A RIFFATERRE SEMIOTIC ANALYSIS - Habibullah, Habibullah; Nensilianti, Nensilianti; Satriani, Irma (Media Inovasi Pendidikan dan Publikasi, 2025)
This study aims to interpret the meaning of signs in the lyrics of Tafsir Mistik by Abyan Zaki using Riffaterre’s semiotic approach. The method used in this research is a descriptive qualitative method. The data and data sources of this study consist of heuristic and hermeneutic readings of the lyrics of Tafsir Mistik by Abyan Zaki. Data collection techniques in this research include documentation, reading, and note-taking. The data analysis techniques applied involve data reduction, data presentation, and drawing conclusions.The results of this study were obtained through heuristic reading, which refers to reading based on linguistic conventions, and hermeneutic reading, which refers to reading based on literary conventions. The song portrays the struggle of humans within an ambiguous space between birth and death, where they often lose direction and succumb to the illusion of false happiness.